Kajian Kegagalan Eksekusi Fidusia Akibat Cacatnya Dokumen Kepemilikan Objek Jaminan - Setiawan, I Ketut Oka; Sriwulan W, R Utji; Paramitha, Deasy (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
This study explores the issue of fiduciary execution failures stemming from defects in ownership documents of collateral objects. The inadequacy or incorrectness of these documents often poses significant obstacles in legal proceedings. The objective is to analyze the factors contributing to the failure of fiduciary execution and their implications for relevant parties. The research methodology includes a detailed examination and a comprehensive literature review to grasp the legal foundations and applicable principles. The findings underscore the critical importance of document clarity and validity in ensuring the efficacy of fiduciary executions. The study concludes with recommendations emphasizing adherence to legal requirements and enhancing awareness and compliance with document standards in fiduciary transactions to mitigate potential legal risks